2013
DOI: 10.1177/1049909113476132
|View full text |Cite
|
Sign up to set email alerts
|

Commonly Prescribed Medications in a Population of Hospice Patients

Abstract: Although much attention has been placed on appropriate symptom management at the end of life, little is known about the medications actually prescribed to people in hospice care. The purpose of this study was to determine the most commonly prescribed medications in a population of hospice patients. A retrospective review of a patient information database was conducted. The 6 most common drugs (acetaminophen, morphine, haloperidol, lorazepam, prochlorperazine, and atropine) were included in emergency kits provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 10 publications
3
61
3
Order By: Relevance
“…However, we also observed that only 68% of patients prescribed an opioid were also prescribed a laxative. The Centers for Medicare & Medicaid Services require that hospices publicly report the percentage of patients treated with an opioid who are offered or prescribed a bowel regimen . Although the Hospice Quality Reporting Program and other studies suggest that hospices are largely meeting this quality metric, our study suggests an opportunity for improvement on discharge to hospice care to reduce the risk of opioid‐induced constipation on hospice admission…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, we also observed that only 68% of patients prescribed an opioid were also prescribed a laxative. The Centers for Medicare & Medicaid Services require that hospices publicly report the percentage of patients treated with an opioid who are offered or prescribed a bowel regimen . Although the Hospice Quality Reporting Program and other studies suggest that hospices are largely meeting this quality metric, our study suggests an opportunity for improvement on discharge to hospice care to reduce the risk of opioid‐induced constipation on hospice admission…”
Section: Discussionmentioning
confidence: 75%
“…Prescribing medications may be particularly challenging during the transition from acute care hospital settings to hospice care because of the often abrupt shift in goals of care and changes in underlying indications for medication use. This is significant because nearly 40% of hospice patients are referred to hospice care from an acute care hospital, and previous large studies suggested that hospice patients receive an average of 10 to 16 medications including several medications with unclear indications in the hospice setting (eg, statins, antithrombotic therapy, and antibiotics) …”
mentioning
confidence: 99%
“…Many patients who receive preventive cardiovascular drugs continue to do so until the very end of life . For example, the prescribing of antihypertensive agents and platelet aggregation inhibitors is commonplace among hospice patients with advanced cancer . Recent studies also have shown that polypharmacy increases near the end of life, which is fueled not only by symptomatic drugs but also by the continuation of preventive agents until the very last weeks of life …”
Section: Discussionmentioning
confidence: 99%
“…26,27 For example, the prescribing of antihypertensive agents and platelet aggregation inhibitors is commonplace among hospice patients with advanced cancer. 28 Recent studies also have shown that polypharmacy increases near the end of life, which is fueled not only by symptomatic drugs but also by the continuation of preventive agents until the very last weeks of life. 18,24 The frequent continuation of long-term preventive drugs is indicative of insufficient deprescribing strategies at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to the polypharmacy burden near the end of life reported by others, however with several key differences. Three studies have previously assessed medication prescribed during end-of-life care (3,18,19). The first, Nauck et al, a representative survey of drugs in palliative care performed in Germany, demonstrated strong opioids as the most common class.…”
Section: Discussionmentioning
confidence: 99%